Suboptimal Blood Pressure Control, Associated Factors, and Choice of Antihypertensive Drugs among Type 2 Diabetic Patients at KCMC, Tanzania - Gabriel W. Mbwete; Kajiru G. Kilonzo; Elichilia R. Shao; Nyasatu G. Chamba (Journal of Diabetes Research)
Background. Hypertension (HTN) can be present in up to two-thirds of patients living with diabetes mellitus (DM). It is a risk factor for the development of diabetes as well as complications like coronary artery disease (CAD), nephropathy, retinopathy, and neuropathy. Hypertension is treatable, and the degree to which it is controlled determines the risk of development of cardiovascular diseases and other complications in a given individual patient. Even though antihypertensive drugs are available and issued to hypertensive diabetic patients, the rate of control of HTN is often inadequate. The aim of this study was to assess the prevalence of suboptimal blood pressure (BP) control, its associated factors, and the choice of antihypertensive drugs among type 2 DM patients at Kilimanjaro Christian Medical Centre (KCMC). Methods. A hospital-based cross-sectional study was conducted at the KCMC diabetes clinic from October 2018 to March 2019 among type 2 DM patients with HTN based on the inclusion criteria. Data were collected using structured questionnaires, and written informed consent was obtained. Suboptimal BP was defined as BP levels≥140/90 mmHg according to the American Diabetes Association guideline published in 2018. Data analysis was done using the Statistical Package for the Social Sciences (SPSS) version 25. Chi-square analysis was done to identify the independent predictors of BP control, and a p value of <0.05 was considered to be statistically significant. Results. The data of 161 participants was analysed; the mean age was 63.9±20.2 years, with the majority being females (67.1%). Despite all participants being on different classes of antihypertensives, 57.8% had suboptimal BP control. Among the participants with good BP control, 52.7% were on angiotensin-converting enzyme inhibitors (ACE-I). Poor diabetes control was observed in 50.1% participants as indicated by elevated glycated haemoglobin. Conclusion. This study demonstrated that BP control in type 2 DM patients was suboptimal in more than half of the participants. The study showed that the use of ACE-I or angiotensin II receptor blockers (ARBs) in the majority of DM patients has a good impact in the control of blood pressure. The early initiation of ACE-I or ARBs among the diabetic patients will improve the optimal BP control.